RESISTENSI NYAMUK Aedes aegypti TERHADAP CYPERMETHRIN DI KABUPATEN KLATEN, JAWA TENGAH - Irawati, Nur Bebi Ulfah; Putri, Novita Eka (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Dengue Hemorrhagic Fever (DHF) is still a global health problem. The Aedes aegypti mosquito transmits DHF, so vector control is an effective strategy in disease prevention. One of the insecticides that have long been used in the Klaten Regency is cypermethrin. However, cases of DHF have been reported to have fluctuated over the past ten years. This study aims to determine the resistance of Ae.aegypti against cypermethrin. Ae.aegypti was obtained from three endemic sub-districts with the highest Ceper District cases, then colonized to the first generation (F1). The CDC bottle bioassay method was applied to determine mosquitoes' resistance status to cypermethrin at a dose of 10 Âµg/ml. The results showed that cypermethrin resistance was found in all samples, from moderate to resistant levels. One sub-district sample showed resistance to cypermethrin (89% mortality after 30 minutes). Two sub-district else showed moderate resistance status (97% mortality after 30 minutes). The continuous use of the insecticide cypermethrin has had a resistance impact on the dengue vector. Community participation in eradicating breeding places is the main form of DHF control and insecticides with various active ingredients.